Meta-analisis Pengaruh Metode Gasing Pada Pembelajaran Matematika SD dalam Meningkatkan Hasil Belajar Siswa - Ari Wicaksono Wibowo; Gustina Dwi Suryaningrum; Nila Ariana Ristianti; Priti Agustin; Putri Prasetyaningtyas (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The background of this research is the low learning outcomes in Mathematics. Because mathematics is considered a difficult subject to understand, and the method given only uses formulas. So that students mostly memorize formulas that make students bored so that learning becomes meaningless. This study aims to analyze the effect of using the gasing method on elementary mathematics learning in improving student learning outcomes. The method used in this study is a meta-analysis method. The research data was obtained by searching online journals through Google Scholar or Google Scholars with the search keywords "The Effect of the Gasing Method", "The Gasing Method", "Elementary Mathematics Learning" and "Mathematics Learning Outcomes". From the search results obtained as many as 22 articles but which are relevant to use only 10 articles. Based on the results of the analysis, the use of the gasing method in elementary mathematics learning can have a good effect in improving student learning outcomes.